FAKTOR YANG MEMPENGARUHI INTELLECTUAL CAPITAL DISCLOSURE PADA PERUSAHAAN LQ45 - Bestyvina Kartika; Merry Susanti (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this research was to examine the influence audit committee’s characteristics and firm characteristics toward intellectual capital disclosure in LQ45 companies listed in the Indonesian Stock Exchange in 2017-2019. The sample was determined by using total sampling method by taking 45 LQ45 companies each year with a total of 135 samples. The data was processed with Eviews 11 by using multiple regression technique. The result showed that audit committee’s meeting frequency had positive effect on intellectual capital disclosure, while audit committee’s size, firm size, profitability, leverage, and industry type had no effect on intellectual capital disclosure. The implication of this study was the need to increase the role of audit committee to increase intellectual capital disclosure and reduce asymmetry information within management and stakeholders.